(untitled) (Medico Legal Update, 2021)
East Java Province has a high prevalence of stunted. The study aimed to analyze the factors associated with stunted in East Java Province. The study was conducted using secondary data sourced from the 2019 East Java Province Health Profile report. The study was designed with an ecological analysis approach. All 38 regencies/cities in East Java Province were analyzed. Apart from the prevalence of stunted toddlers as the dependent variable, 4 other variables were analyzed as independent variables, namely the coverage of toddler health services, Universal Child Immunization (UCI) village coverage, coverage of families accessing healthy latrines, and percentage of samples of drinking water facilities that meet the requirements. The results showed that the trend of regencies/cities with low coverage of toddler health services has a high prevalence of stunted toddlers. There was a tendency for regencies/cities that have a higher level of immunization coverage which tends to have a lower percentage of stunted toddlers. Meanwhile, the trend of regencies/cities that have better coverage of families accessing healthy latrines has a lower prevalence of stunted toddlers. Finally, regencies/cities with a high percentage of babies receiving exclusive breastfeeding have the lowest prevalence of babies receiving exclusive breastfeeding. It could be concluded that there is a tendency for a negative relationship between the independent variables analyzed and the prevalence of stunted toddlers. The higher the coverage on the independent variable, the lower the tendency for the coverage percentage to be stunted in East Java Province.